The effect of support condition on dynamic parameters - Fayyadh, M.M.; Razak, H.A. (2010)
Bridge girders are normally supported on rubber bearings which are subjected to deterioration during the life span of the bridge. Early deterioration of the bearings results in decrease of its stiffness while advanced deterioration can cause total damage of the bearings, whereby the bridge girders will be directly supported on the structural element below it. This paper reports an investigation on the effect of support condition on the dynamic parameters of a simply supported beam. Experimental modal analysis was conducted on the beam under different support stiffness with new and old rubber bearings and without rubber bearings. The natural frequencies and mode shapes were acquired from the test and compared using various algorithms as indicators for the state of the supports. From the results, the flexural natural frequencies showed good sensitivity to the support conditions which makes it a feasible tool for health monitoring purposes. This is applicable to all the bending modes with the exception of mode 3 which showed an opposite trend. The lower modes had higher sensitivity to the differences in support condition and it can be concluded that mode 1 was more reliable in assessing the boundary conditions.